2022
DOI: 10.1101/2022.01.24.477597
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unadjuvanted intranasal spike vaccine booster elicits robust protective mucosal immunity against sarbecoviruses

Abstract: As the SARS-CoV-2 pandemic enters its third year, vaccines that not only prevent disease, but also prevent transmission are needed to help reduce global disease burden. Currently approved parenteral vaccines induce robust systemic immunity, but poor immunity at the respiratory mucosa. Here we describe the development of a novel vaccine strategy, Prime and Spike, based on unadjuvanted intranasal spike boosting that leverages existing immunity generated by primary vaccination to elicit mucosal immune memory with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 46 publications
2
51
0
Order By: Relevance
“…However, continued SARS-CoV-2 evolution will accentuate the genetic drift from the ancestral strain and it is unknown if vaccines based on Wuhan-Hu-1 S alone will provide satisfactory protection, either as boosters in experienced individuals or as an initial vaccine in naive individuals (mainly children). The recent evaluation of intranasal vaccine administration could also be important to not only prevent severe disease but also curtail viral infection and transmission through induction of mucosal immunity ( 59, 60 ). For these reasons, it is important to monitor new variants, assess the effectiveness of currently available vaccines, and continue to test and implement new vaccination strategies that may provide stronger, longer lasting, or broader protection against SARS-CoV-2 and the entire sarbecovirus subgenus ( 38, 61, 62 ).…”
mentioning
confidence: 99%
“…However, continued SARS-CoV-2 evolution will accentuate the genetic drift from the ancestral strain and it is unknown if vaccines based on Wuhan-Hu-1 S alone will provide satisfactory protection, either as boosters in experienced individuals or as an initial vaccine in naive individuals (mainly children). The recent evaluation of intranasal vaccine administration could also be important to not only prevent severe disease but also curtail viral infection and transmission through induction of mucosal immunity ( 59, 60 ). For these reasons, it is important to monitor new variants, assess the effectiveness of currently available vaccines, and continue to test and implement new vaccination strategies that may provide stronger, longer lasting, or broader protection against SARS-CoV-2 and the entire sarbecovirus subgenus ( 38, 61, 62 ).…”
mentioning
confidence: 99%
“…Mucosal vaccination strategies have been shown to improve upon systemic vaccination through the induction of tissue resident memory T and B cells, which can rapidly respond to viral invasion into the respiratory tract (31, 63). Additionally, mucosal vaccination can induce higher levels of antibodies in the respiratory mucosa (59). The induction of robust mucosal cellular and humoral immunity can more rapidly neutralize viruses upon entry into the respiratory tract, thereby preventing both infection and transmission (60).…”
Section: Discussionmentioning
confidence: 99%
“…The respiratory tract is the site of invasion and primary site of replication and disease manifestation for SARS-CoV-2 and its variants. Several studies investigating viral vector and protein-based vaccines have demonstrated that superior mucosal immunity can be achieved through direct antigen presentation across the mucosal surface of the lung (59)(60)(61)(62). Mucosal vaccination strategies have been shown to improve upon systemic vaccination through the induction of tissue resident memory T and B cells, which can rapidly respond to viral invasion into the respiratory tract (31,63).…”
Section: Discussionmentioning
confidence: 99%
“…From a biological point of view, the currently licensed vaccines are administered intramuscularly which means that immune protection against virus is difficult to achieve in the primary and secondary sites of infection, i.e. the nasal and upper respiratory tract passages, respectively 26 . For these reasons, intranasal administration of the vaccine formulated as a convenient nasal spray might offer an attractive solution to both problems.…”
Section: Discussionmentioning
confidence: 99%
“…Intranasal vaccines may address this issue via enhancement of localized nasal mucosal immunity and local immunological memory. This approach appears to be promising based on recent animal studies with a nasal spray version of ChAdOx nCoV-19 administered as two doses of primary vaccination or a Prime and Spike approach using mRNA intramuscular vaccine as a Prime followed by recombinant unadjuvanted spike protein by IN administration, as well as broad sarbecovirus mucosal immunity conferred by unadjuvanted recombinant spike protein delivered via mRNAliponanoparticle 26,27 . MVC-COV1901 is a protein subunit vaccine based on stable prefusion SARS-CoV-2 spike protein S-2P adjuvanted with CpG 1018 and aluminum hydroxide 28 .…”
Section: Introductionmentioning
confidence: 99%